(untitled) - Yanis, Edward M. (New York, 2002)
It may be a truism that investors can't outperform the market in the long run, yet Edward M. Yanis, chairman of Yanis Financial Services, claims to have beat the system. His book Riding the Bull, Beating the Bear: Market Timing for the Long-Term Investor describes the "Y-Process," a mathematical model that supposedly allows investors to predict the upcoming fluctuations of the market. Yanis cautions, however, that this technique is only for "sophisticated" investors, and much of the book is taken up with more conservative and familiar advice (diversification, mutual funds) for beginner and intermediate players
Keywords: Investment analysis,Stock price forecasting,Portfolio management,Quản lý vốn đầu tư,Dự báo chứng khoán